Cultural Intelligence: o impacto da experiência internacional no nível de inteligência cultural dos alunos da Universidade de Caxias do Sul - Suzin, Lia Francini (My University, 2021)
International experience provides individuals with different kinds of opportunities that other experiences would not. A higher level of cultural intelligence is one of these opportunities and it is up to each one to use a broader worldview in favor of your own self and other cultures, both personally and professionally. Thus, measuring people's cultural intelligence is an important step to start the trajectory of each individual within the scope of knowing themselves and the cultural capacity of each one. This research aims to identify how the international experience affects the level of Cultural Intelligence of undergraduate students at the University of Caxias do Sul. The level of students? Cultural Intelligence from the most varied undergraduate courses was measured through The Expanded Cultural Intelligence Scale, with a sample of 174 respondents, 52 of whom have previous international experience, with different periods living abroad and different types of international experience. Analyzing the averages and their respective statistical importance, it was concluded that, in fact, students who have international experience have a higher level of Cultural Intelligence. [resumo fornecido pelo autor]
A experiência internacional provê aos indivíduos diferentes oportunidades que outras experiências não trariam. Um maior nível de inteligência cultural é uma dessas oportunidades e cabe a cada um utilizar essa visão de mundo mais ampla a seu favor e a favor de outras culturas, seja no âmbito pessoal e também no profissional. Dessa forma, medir a inteligência cultural das pessoas é um passo importante para iniciar a trajetória de cada indivíduo no âmbito de conhecer a si próprio e a capacidade cultural de cada um. Esta pesquisa tem a finalidade de identificar de que forma a experiência internacional afeta o nível de Inteligência Cultural dos alunos de graduação da Universidade de Caxias do Sul. Através da Escala de Inteligência Cultural Expandida (The Expanded Cultural Intelligence Scale), foi medido o nível de Inteligência Cultural dos alunos dos mais variados cursos de graduação com uma amostragem de 174 respondentes, sendo que 52 desses alunos possuem experiência internacional prévia, com diferentes tempos de permanência no exterior e diferentes tipos de experiência internacional. Analisando as médias e suas respectivas importâncias estatísticas, chegou-se a conclusão que, de fato, alunos que possuem experiência internacional possuem um maior nível de Inteligência Cultural. [resumo fornecido pelo autor]
Keywords: Comércio internacional; Inteligência cultural